2007
DOI: 10.1002/anie.200604176
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Mutarotation into Induced Circular Dichroism Signals through Helix Inversion of Host Polymers

Abstract: One of the most exciting and challenging topics in molecular recognition is the development of artificial host molecules that recognize saccharides in aqueous protic media through the formation of hydrogen bonds. [1,2] We recently designed and synthesized water-soluble meta-ethynylpyridine polymers such as 1 (Scheme 1) [3] which spontaneously form helical structures in protic media through intramolecular solvophobic interactions. [3,4] This organization forces the pyridine N atoms to be positioned on the insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…It was thus suggested that the origin of the altered CD signals was the helix inversion of the host polymer ( Fig. 7), rather than partial dissociation of the complex [85]. It was then postulated that the different stereochemical configurations of C1 in glucoses, ␣ and ␤, led poly(m-ethynylpyridine) to adopt helical conformations of opposite handedness, which was illustrated by opposite signs and different magnitudes (i.e., −3 and +7 mdeg, respectively) of the initial CD signals.…”
Section: Poly-and Oligo(meta-ethynylpyridine)s As Helical Hosts For Smentioning
confidence: 97%
“…It was thus suggested that the origin of the altered CD signals was the helix inversion of the host polymer ( Fig. 7), rather than partial dissociation of the complex [85]. It was then postulated that the different stereochemical configurations of C1 in glucoses, ␣ and ␤, led poly(m-ethynylpyridine) to adopt helical conformations of opposite handedness, which was illustrated by opposite signs and different magnitudes (i.e., −3 and +7 mdeg, respectively) of the initial CD signals.…”
Section: Poly-and Oligo(meta-ethynylpyridine)s As Helical Hosts For Smentioning
confidence: 97%
“…Moreover, carbohydrate recognition in organic media can be biomimetic in the sense of mimicking recognition at the membrane-cytosol interface, especially if extraction from water can be demonstrated. Accordingly, there has been considerable work in this area over the past 20 years, as recorded in a number of reviews [24,36,48,49] and recent articles [50][51][52][53][54][55][56][57][58][59]. For reasons of space, we will not attempt a further discussion of this work but will proceed to our major topic of carbohydrate recognition in water.…”
Section: Synthetic Lectin Design Principlesmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] These objects have until now been much smaller and far less complex than proteic receptors. Nevertheless, they share with them a vast potential for tunability: they are based on sequences whose monomers can be changed one at a time and introduced by using the same synthetic methods.…”
Section: Introductionmentioning
confidence: 99%